Ambiguity Found In Passport To The World 2: A Fun AndEasy English Book: Content Analysis - Rekha, Agnira; , Prof. Dr. Endang Fauziati, M. Hum; , Mauly Halwat Hikmat, Ph. D (2014)
This study deals with the ambiguity which is found in Passport to the World 2 English Book. The aims of this study are (1) to describe the types of ambiguity, (2) to describe the frequency of each type of ambiguity, (3) to describe the dominant type of ambiguity this dominantly appears, (4) to describe the causes of ambiguity, and (5) to describe the way to disambiguate ambiguity found in Passport to the World 2 English Book. The type of this research is descriptive qualitative research. The data source of this research is ambiguous words, phrases and sentences found in Passport to the World 2 English Book. The data collection technique is documentation. The technique of data analysis are descriptive qualitative. The writer uses the theories from Kess in Fauziati, Kreidler, Fromkin, Roadman and Hyme to analyze the types of ambiguity. The result of this study shows that (1) the writer found four types of ambiguity namely: lexical ambiguity, referential ambiguity, surface structure ambiguity, and deep structure ambiguity; (2) the frequency of each type of ambiguity are 73 lexical ambiguity (64,03%), 25 referential ambiguity (21,93 %), 15 surface structure ambiguity (13,16 %) and 1 deep structure ambiguity (0, 88%); (3) the dominant types of ambiguity is lexical ambiguity; there are 73 ambiguous sentences or 64, 03%; (4) the causes of ambiguity are without context, ambiguous word order, improper or missing punctuation, and faulty sentence construction; (5) the way to disambiguate ambiguity are using paraphrasing, truth conditional sentences, adding preposition, moving sentence construction, adding additional context, adding correct punctuation and using picture.